Examining the impact of leisure internet use and study–leisure conflict on university students’ academic achievement - Vapur, Muhammet; Güven, Yiğit (Jurnal Cakrawala Pendidikan, 2026)
The aim of this study is to examine the effects of university students’ internet usage during their leisure time and their study–leisure conflicts on academic achievement. The study was conducted using a quantitative, correlational research design, and the sample consisted of 392 students studying at universities in Istanbul, selected through simple random sampling. Data were collected using three scales: the Leisure-Time Internet Use Scale, the Study/Leisure Conflict Scale, and the Academic Achievement Scale. According to the results of regression analyses, the level of internet use during leisure time explains 26.2% of the variance in study–leisure conflict and 13.1% of the variance in academic achievement. Additionally, study–leisure conflict was found to be a significant predictor of academic achievement, accounting for 19.9% of the variance. The findings suggest that students’ digital leisure habits have both direct and indirect effects on time management, self-regulation, and academic balance. The results highlight the need for digital awareness programs and time management support services in universities. This study aims to contribute to educational policies by shedding light on the psychosocial processes that influence students’ academic success in the digital age.